Effectiveness of various interventions on maintenance of gingival health during 1 year – a randomized clinical trial. Issue 4 (8th March 2016) - Van Leeuwen, MPC; Rosema, NAM; Versteeg, PA; Slot, DE; Hennequin‐Hoenderdos, NL; Van der Weijden, GA
Abstract: Background: Rinsing with the combined use of an oxygenating‐agent (OA) and chlorhexidine (CHX) in addition to mechanical oral hygiene could improve and/or maintain good gingival health over a long period. Methods: This study had an examiner‐blinded, randomized, six‐group parallel design consisting of two‐phases: a 3‐week treatment phase and a subsequent 12‐month experimental phase. A total of 267 subjects in good general health (≥18 years), without periodontitis, with at least five teeth per quadrant, and with moderate to advanced gingivitis were enrolled. A 3‐week treatment phase was initiated to improve gingival health. Subjects were assigned to one of the six groups: two basic oral hygiene groups (Control I & II), one professional oral hygiene instruction group (OHI), one professional prophylaxis group (PP), an OA&CHX rinse group and a group receiving a combination of all regimens (COMBI group), being OHI + PP + OA&CHX. Dental plaque, gingival bleeding and staining assessments were performed at the start of the treatment phase, at baseline and at 4, 7, 10, and 12 months. Results: There was a significant reduction in dental plaque‐scores for the OA&CHX and COMBI‐group (0.51 [SD = 0.37], 0.38 [SD = 0.33] respectively) and a significant reduction in gingivitis scores for the OA&CHX and COMBI group (6.9% [SD = 14.0], 13.4% [SD = 13.4] respectively) from the start of the treatment phase to baseline. No clinically relevant changes were observed for the other four groups. After baseline, bleeding and plaque‐scores increased back to a non‐significant level between groups, and this level remained throughout the study. Conclusion: OA&CHX and COMBI‐group showed a clinically relevant improvement after the treatment phase in terms of dental plaque and gingival bleeding levels. At the 4‐month clinical assessment, there was no longer a significant difference between groups.